Effectiveness of COVID-19 mRNA Vaccines in Preventing COVID-19-Associated Outpatient Visits and Hospitalizations Among American Indian and Alaska Native Persons, January–November 2021: A Test-Negative Case–Control Analysis Using Surveillance Data. (27th March 2023) - Lutz, Chelsea S; Hartman, Rachel M; Vigil, Deionna E; Britton, Amadea; Burrage, Amanda B; Campbell, Angela P; Close, Ryan M; Desnoyers, Christine; Dobson, Jennifer; Garcia, Starla; Halasa, Natasha; Honie, Elvira; et al.
Abstract: Background: Despite the disproportionate morbidity and mortality experienced by American Indian and Alaska Native (AI/AN) persons during the coronavirus disease 2019 (COVID-19) pandemic, few studies have reported vaccine effectiveness (VE) estimates among these communities. Methods: We conducted a test-negative case–control analysis among AI/AN persons aged ≥12 years presenting for care from January 1, 2021, through November 30, 2021, to evaluate the effectiveness of mRNA COVID-19 vaccines against COVID-19-associated outpatient visits and hospitalizations. Cases and controls were patients with ≥1 symptom consistent with COVID-19-like illness; cases were defined as those test-positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), and controls were defined as those test-negative for SARS-CoV-2. We used unconditional multivariable logistic regression to estimate VE, defined as 1 minus the adjusted odds ratio for vaccination among cases vs controls. Results: The analysis included 207 cases and 267 test-negative controls. Forty-four percent of cases and 78% of controls received 2 doses of either BNT162b2 or mRNA-1273 vaccine. VE point estimates for 2 doses of mRNA vaccine were higher for hospitalized participants (94.6%; 95% CI, 88.0–97.6) than outpatient participants (86.5%; 95% CI, 63.0–95.0), but confidence intervals overlapped. Conclusions: Among AI/AN persons, mRNA COVID-19 vaccines were highly effective in preventing COVID-associated outpatient visits and hospitalizations. Maintaining high vaccine coverage, including booster doses, will reduce the burden of disease in this population.